Tenebrio molitor PGRP-LE Plays a Critical Role in Gut Antimicrobial Peptide Production in Response to Escherichia coli - Keshavarz, Maryam; Jo, Yong Hun; Edosa, Tariku Tesfaye; Han, Yeon Soo (Frontiers in Physiology, 2020)
Invading pathogens are recognized by peptidoglycan recognition proteins (PGRPs) that induce translocation of NF-κB transcription proteins and expression of robust antimicrobial peptides (AMPs). Tenebrio molitor PGRP-LE (TmPGRP-LE) has been previously identified as a key sensor of Listeria monocytogenes infection. Here, we present that TmPGRP-LE is highly expressed in the gut of T. molitor larvae and 5-day-old adults in the absence of microbial infection. In response to Escherichia coli and Candida albicans infections, TmPGRP-LE mRNA levels are significantly upregulated in both the fat body and gut. Silencing of TmPGRP-LE by RNAi rendered T. molitor significantly more susceptible to challenge by E. coli infection and, to a lesser extent, Staphylococcus aureus and C. albicans infections. Reduction of TmPGRP-LE levels in the larval gut resulted in the downregulation of eight AMP genes following exposure to E. coli, S. aureus, and C. albicans. However, the transcriptional levels of AMPs more rapidly reached a higher level in the dsEGFP-treated larval gut after challenge with E. coli, which may suggest that AMPs induction were more sensitive to E. coli than S. aureus and C. albicans. In addition, TmPGRP-LE RNAi following E. coli and C. albicans challenges had notable effects on TmRelish, TmDorsal X1 isoform (TmDorX1), and TmDorX2 expression level in the fat body and gut. Taken together, TmPGRP-LE acts as an important gut microbial sensor that induces AMPs via Imd activation in response to E. coli, whereas the involvement of TmPGRP-LE in AMPs synthesize is barely perceptible in the hemocytes and fat body.